Neoextractivism. Debates and conflicts in countries with progressive governments in South America - Lander, Edgardo (2017)
The specialization in the production of raw materials, far from allowing an accumulation that guarantees the investment in alterna-tives to the extractivism, tends to block the possibility of other activities generating processes of deindustrialization in the continent, and the deterioration of the food sovereignty. With this no alternatives to capitalism are being built, not even putting obstacles, but feeding their insatiable predatory machinery.